# Calculus

Solve the integral: ∫ x^3/(x^+2)^2

I'm stuck. This is my work so far.

∫ A/(x^+2) + ∫ B/(x^2-2)^2
F(x)=A ln(x^2+2)-B/(x^2+2)+C
X^3=A(x^2+2)+B

1. 👍 0
2. 👎 0
3. 👁 39
1. let z = x^2+2 then dz = 2x dx and dx = dz/2x and x = (z-2)^.5 and xdx=dz/2
so x^2 = (z-2)
now what you have is
∫ (z-2) x dx/z^2 = ∫ (z-2)dz /2z^2
= ∫ dz/2z - ∫ dz/z^2

1. 👍 0
2. 👎 0
posted by Damon

## Similar Questions

1. ### calc II

Express the integrals as the sum of partial fractions and evaluate the integral: (integral of) (x^2)dx/(x-1)(x^2 +2x+1) My work: The above integral is equal to x^2dx/(x+1)^2 (A/x-1) + (B/x+1) + (Cx+D)/(x+1)^2 = x^2 A(x+1)^2 +

asked by Jenna on December 6, 2009
2. ### Calculus - Seperable Equations

Solve the separable differential equation (dy/dx)=y(1+x) for y and find the exact value for y(.3). dy/dx = y(1+x) dy/y = (1+x)dx Integral (dy/y) = Integral (1+x)dx ln (y) = x + (1/2)x^2 + C y = e^(x + (1/2)x^2 + C) y(0.3) =

asked by COFFEE on June 26, 2007
3. ### calc: arc length

find the exact length of this curve: y = ( x^3/6 ) + ( 1/2x ) 1/2

asked by COFFEE on June 11, 2007
4. ### Calc

Evaluate the integral using any method: (Integral)sec^3x/tanx dx I started it out and got secx(1tan^2x)/tanx. I know I just have to continue simplifying and finding the integral, but I'm stuck on the next couple of steps. Also, I

asked by H on October 1, 2012
5. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006
6. ### Calculus

I'm doing statistics homework and am stuck on a problem using integration. The problem gives a distribution where for x>1, f(x) = k x^-6. I am then asked to "Determine the value of k for which f(x) is a legitimate pdf. " To be a

asked by Paul on September 27, 2007
7. ### Calculus

Solve the integral (x+3)/(x-1)^3 So far, I'm stuck. This is what I have thus far: x+3 = A(x-1)^3/(x-1) + B(x-1)^3/(x-1)^2 + C(x-1)^3/(x-1)^3 x+3 = A(x^2-2x+1) + B(x-1) + C x+3 = Ax^2 - 2Ax +Bx + A - B + C x+3 =Ax^2 + 1(B-2A)x + (A

asked by Mike on September 22, 2018
8. ### Calculus

Can someone check my work and answer? Evaluate the integral from -1 to 0 of (4x^6+2x)^3(12x^5+1)dx My work: let u=4x^6+2x dx=du/24x^5+2 now we have the integral from -1 to 0 of u^3(12x^5+1)(du/24x^5+2) Simplifies to the integral

asked by Liz on February 18, 2018
9. ### math

How do I derive the secant reduction rule? Integral (sec x)^n dx = Integral (sec x)^(n-2) * (sec x)^2 dx = Integral ((tan x)^2 + 1)^(n/2-1) * (sec x)^2 dx Doing a substitution with: u = tax x du = (sec x)^2 dx = Integral (u^2 +

asked by mathstudent on November 7, 2007
10. ### Physics

Suppose we had a straight tunnel, through Earth's center, to a point on the opposite side of the planet, and used it to deliver mail to the other side. With what speed would our packages pass through Earth's center. So: ag =

asked by Nora on April 4, 2015

More Similar Questions